Pre-retinal delivery of recombinant adeno-associated virus vector significantly improves retinal transduction efficiency - Hanmeng Zhang; Benjamin S. Sajdak; Dana K. Merriman; Joseph Carroll; Daniel M. Lipinski (Molecular Therapy: Methods & Clinical Development, 2021)
Intravitreal injection is the most widely used injection technique for ocular gene delivery. However, vector diffusion is attenuated by physical barriers and neutralizing antibodies in the vitreous. The 13-lined ground squirrel (13-LGS), as in humans, has a larger relative vitreous body volume than the more common rodent models such as rats and mice, which would further reduce transduction efficiency with the intravitreal injection route. We report here a “pre-retinal” injection approach that leads to detachment of the posterior hyaloid membrane and delivers vector into the space between vitreous and inner retina. Vectors carrying a ubiquitously expressing mCherry reporter were injected into the deep vitreous or pre-retinal space in adult wild-type 13-LGSs. Then, adeno-associated virus (AAV)-mediated mCherry expression was evaluated with non-invasive imaging, immunofluorescence, and flow cytometry. Compared to deep vitreous delivery, pre-retinal administration achieved pan-retinal gene expression with a lower vector dose volume and significantly increased the number of transduced cone photoreceptors. These results suggest that pre-retinal injection is a promising tool in the development of gene therapy strategies in animal models and is a potential approach for use in human research, particularly in younger individuals with an intact posterior hyaloid membrane and stable vitreous.